Recent Advances in Nickel Ferrite-Polymer Nanocomposites for Radar Absorbing Material Applications - Thesalonika Br Panjaitan; Alya Hijrianisa; Yusuf Bramastya Apriliyanto; Dea Dwi Ananda; Rahmat Basuki; Hotma Renta (Indonesian Scholar Society, 2025)
Nickel ferrite (NiFe₂O₄) and its polymer-based composites have emerged as promising candidates for radar absorbing materials (RAMs) due to their unique combination of magnetic and dielectric loss mechanisms. This review highlights recent advances in synthesis strategies, including sol–gel, hydrothermal, co-precipitation, and microwave-assisted methods, which enable precise control of particle size, morphology, and crystallographic defects. Such control supports flexible structural design of nickel ferrite spinel structures, allowing dopant incorporation to tailor magnetic anisotropy and saturation magnetization. These structural features directly affect electromagnetic performance. Magnetic loss is mainly governed by natural resonance and, to a lesser extent, eddy current effects, while dielectric loss arises from dipole polarization, interfacial polarization, and conduction loss. The synergistic balance of magnetic and dielectric losses makes nickel ferrite–polymer nanocomposites promising broadband radar absorbing materials. The discussion emphasizes the role of cation substitution, polymer matrices, and hybridization with carbon-based materials in enhancing microwave absorption bandwidth and impedance matching. Various synthesis approaches, including sol–gel, hydrothermal, and in-situ polymerization, are compared with respect to their influence on particle size, morphology, and absorption efficiency. Challenges such as limited bandwidth, thermal and mechanical stability, and scalability are highlighted, along with potential solutions through advanced nanostructuring, multifunctional design, and sustainable synthesis. Future research directions are also outlined to support the development of next-generation stealth and electromagnetic interference shielding technologies.